Wind power plants : Fundamentals, design, construction and operation. - Gasch, R., ....-; Twele, J., ....- (Berlin : Solarpraxis, 2002)
- Introduction to wind energy - Historical background Wind turbines - design and components - The wind - Wind turbine dimensioning - Calculation of performance characteristics and partial loads behaviour - Structural loads and strength issues - Scaling wind turbines and rules of similarity - Wind-pumping systems - Power generation - Control of wind turbines - Dynamic problems of wind turbines - Offshore wind farms "Wind Power Plants" is essential reading for anyone working in or interested by wind energy, including planning engineers, consultants on renewable energy projects, manufacturers of turbines and components, researchers and students of wind energy. This book includes contributions from fourteen experts in academia and industry. Prof. Dr.-Ing. Robert Gasch and Dr.-Ing. Jochen Twele, the book's editors, have been lecturing in wind power since 1984 at the Technical University of Berlin, Germany
Keywords: Windenergie